2015
DOI: 10.1097/aci.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, allergy and the Olympics

Abstract: OBJECTIVE: There are no comprehensive surveys relating the reported high prevalence of asthma and allergic diseases in athletes to comorbidities and immune changes associated with intense chronic exercise. This 12-year survey aims to evaluate several clinical, functional and immunological parameters in order to assess features, trend and burden of asthma, allergy, infections and autoimmune diseases, in a large homogeneous population of Olympic athletes. METHODS: Six hundred and fiftynine Italian Olympic athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Moreover, if this form of exercise is undertaken regularly, so that age-specific guidelines concerning the recommended duration and frequency of exercise are met (e.g., 30 min of moderate intensity exercise on 5 days of the week for adults), the result is a better functioning immune system and a lower incidence of disease (Arem et al 2015 ; Lee et al 2012 ; World-Health-Organisation 2010 ). Conversely, some evidence shows that long-duration one-off bouts of exercise (e.g., marathon running, especially if this is unaccustomed) and weeks or months of very high-intensity long-duration athletic training, sometimes referred to as “overreaching” or “over-training”, are associated with an increased risk of certain infections, suggesting compromised immunity (Bonini et al 2015 ; Derman et al 2014 ; Gleeson and Walsh 2012 ; Meeusen et al 2013 ). At the far end of this scale, it is known that extreme exercise, such as ultra-endurance races (i.e., exercise performed over large parts of a day or several consecutive days with little or no rest), is associated with very large, and sometimes prolonged, immunological and inflammatory disturbances (Turner et al 2011 , 2013 ).…”
Section: Associations Between the “Dose” Of Exercise Immune Functionmentioning
confidence: 99%
“…Moreover, if this form of exercise is undertaken regularly, so that age-specific guidelines concerning the recommended duration and frequency of exercise are met (e.g., 30 min of moderate intensity exercise on 5 days of the week for adults), the result is a better functioning immune system and a lower incidence of disease (Arem et al 2015 ; Lee et al 2012 ; World-Health-Organisation 2010 ). Conversely, some evidence shows that long-duration one-off bouts of exercise (e.g., marathon running, especially if this is unaccustomed) and weeks or months of very high-intensity long-duration athletic training, sometimes referred to as “overreaching” or “over-training”, are associated with an increased risk of certain infections, suggesting compromised immunity (Bonini et al 2015 ; Derman et al 2014 ; Gleeson and Walsh 2012 ; Meeusen et al 2013 ). At the far end of this scale, it is known that extreme exercise, such as ultra-endurance races (i.e., exercise performed over large parts of a day or several consecutive days with little or no rest), is associated with very large, and sometimes prolonged, immunological and inflammatory disturbances (Turner et al 2011 , 2013 ).…”
Section: Associations Between the “Dose” Of Exercise Immune Functionmentioning
confidence: 99%
“…Several mechanisms can be implicated for this risk, which include the interplay between environmental training factors (allergens, temperature, air pollution) and athlete's personal risk factors, such as genetic susceptibility, neurogenic-mediated inflammation and epithelial sensitivity. Chronic and intense physical exercise may cause transient immunodepression with a preferential shift to a Th2 response, associated with the development of allergic reactions (Bonini et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Overall, we found that the prevalence of EIB was reported in a total of 35 of the 60 reviewed studies, using a combination of the methods listed above. The studies, main findings, and ratio of male and female enrolled subjects are summarized in Table 1 [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Collectively, these studies enrolled 5103 athletes and reported a diagnosis of EIB in 1153 subjects.…”
Section: Resultsmentioning
confidence: 99%